Tribological and Micromechanical Properties of the Nanostructured Carbonitride/Nitride Coatings of Transition Metals Alloyed by Hf and Nb - Leitans, Armands; Jansons, Ernests; Lungevics, Janis; Kundzins, Karlis; Boiko, Irina; Kanders, Uldis; Kovalenko, Vladimirs; Linins, Oskars (MDPI, 2023)
In this article, the fabrication, characterization, tribological performance, and micromechanical properties of nanostructured smart coatings (NSC) based on the multilayered alternating carbonitride/nitride bilayer {TiMe-CN/TiAlSi-N}n system are discussed. The symbol “Me” denotes refractory metals Hf or Nb, and the index “n” shows the number of superlattice periods. The NSC samples were deposited onto bearing steel (100Cr6) substrates using a reactive high-power physical vapor deposition (PVD) technique that can be scaled up for industrial use. The deposited multilayered NSC contained crystalline nanometer-scale TiMe-CN/TiAlSi-N nanoparticles strengthened by Hf or Nb additives, which increased surface microhardness up to 3000 HV. The measured steady-state friction coefficient (CoF) was within the 0.2–0.4 range, and a specific wear rate lower than 2 × 10−6 mm3/Nm was observed in the dry friction regime. The impact of NSC substrate hardness and NSC coating thickness on microhardness measurement values was investigated. A thicker coating provided a higher integrated (coating + substrate) microhardness value at a lower indentation test force (<0.3 N). As the indentation test force increased, the obtained microhardness values decreased faster for the coatings deposited on a softer substrate. The surface roughness impact on wear properties for specific NSC coatings was observed. --//-- This is an open-access article Leitans, A.; Jansons, E.; Lungevics, J.; Kundzins, K.; Boiko, I.; Kanders, U.; Kovalenko, V.; Linins, O. Tribological and Micromechanical Properties of the Nanostructured Carbonitride/Nitride Coatings of Transition Metals Alloyed by Hf and Nb. Coatings 2023, 13, 552. https://doi.org/10.3390/coatings13030552 published under the CC BY 4.0 licence.
This research was funded by the Latvian Council of Science, project “Carbon-rich self-healing multifunctional nanostructured smart coatings (NSC) for high-tech applications using high-power confined plasma technology for their deposition”, project No. 2019/1-0385.
Keywords: Research Subject Categories::NATURAL SCIENCES::Physics; carbonitride/nitride coatings; superlattice; micro-indentation; microhardness; tribological performance; wear; friction coefficient; surface texture